Producción de celulasas bacterianas termoestables utilizando papel periódico reciclado como sustrato - Ramirez Arua, Héber Esaú (2017)
From 18 bacterial cultures, a selection was made on two levels. The first, based on the qualitative nature of the activity of cellulases, whose selection indicator was the largest hydrolysis zone in solid media production with periodic paper, which resulted in a subselection of 4 bacteria. The second, based on the quantitative character of the activity of the enzymes, whose selection indicator was the highest total cellulase activity (FPU.mL-1 ), generating a selective bacterium, CB-13; Which was identified molecularly by sequencing its 16S rRNA gene exhibiting a similarity to 99% and 97% with the partial sequence of the 16S rRNA gene from Geobacillus thermoparaffinivorans strain Ba3 and Geobacillus thermoparaffinivorans strain Et2 / 4, respectively. This bacterium was applied in submerged fermentation, where by means of the application of the experimental designs of Plackett-Burman and Box-Behnken, an attempt was made to improve the production of enzyme; The composition of the improved medium in % (w/v) was: old newspaper 0,30; lactose 0,25; sucrose 0,25; (NH4) 2SO4 1,17; CaCl2 0,06; yeast extract 0,2; MgSO4.7H2O 0,11; KH2PO4 0,90; peptone 0,15; pH 6,5; culture temperature at 60 °C and incubation time 72 hours. The same that generates an average yield of 97.44 FPU per milligram of dry substrate. It was attempted to separate and purify the β-glucosidase, by chromatography and its respective electrophoretic analysis of the resulting fractions, obtaining its approximate molecular weight 92,6 kDa. xxi Finally, the functional characterization of the total cellulases was performed, showing the pH of 7,0 and the temperature of 70 °C as optimum for the activity. In addition, the thermostability was evaluated, resulting stable for approximately 4 hours at a temperature of 70 ° C and 2 hours at 80 °C. I. INTRODUCCIÓN La producción de celulasas, a partir de material lignocelulósico, se intentó por muchos investigadores. Hoy en día, esto se debe